اسلامی ریاست میں امن و استحکام کے ایجابی اقدامات: The Positive Steps for the Peace and Stability in the Islamic State - Zahid, Dr. Ghulam Rasool; AL-AZHARI, Dr. Manzoor Ahmed (Al-Irfan, 2023)
An Islamic state is responsible to enforce glorious Quranic principles encompassing positive strategies to generate an atmosphere of peace and tranquility for its citizens. These positive steps, alongwith negative measures against threats to societal peace, ensure protection and security at each and every level. These positive measures, as ordained by Islam, include protection of fundamental human rights, establishment of social justice system, policy of mutual consultation and assignment of key positions to eligible individuals. The state is bound by Quranic guidance to encourage freedom of speech and expression of positive opinions through all available sources and means, including political parties, pressure groups and different plate forms. However, this freedom of speech is subject to unbiased commitment to Islamic principles, sincerity of purpose and intentions of honesty and well wishing. Islamic state is essentially a positive state whose Constitution, laws, rules and policies contain constructive positivity in essence.